A Bird's-Eye View of Exercise Intervention in Treating Depression Among Teenagers in the Last 20 Years: A Bibliometric Study and Visualization Analysis - You, Yanwei; Wang, Dizhi; Wang, Yuning; Li, Zhipeng; Ma, Xindong (Frontiers in Psychiatry, 2021)
Background: Exercise is medicine. Multiple studies on the effects and mechanisms of exercise in treating depression among teenagers and adolescents have been widely reported. However, literature involving scientometric analysis of this topic is sparse. Here, we pioneered to conduct a bibliometric study and visualization analysis to give a bird’s-eye view of the publications between 2000 and 2020 on exercise therapy treating depression. Methods: Relevant original publications were obtained from the Science Citation Index Expanded in the Web of Science Core Collection (WoSCC) database between 2000 and 2020. CiteSpace (5.7.R 5) and VOSviewer (1.6.16) software were used to perform bibliometric analysis of countries, institutions, categories, journals, authors, references and keywords involved in this topic. Results: A total number of 975 articles on this field were retrieved from the WoSCC database and we identified an overall increase in the amount of publications over the past two decades, with the United States and Harvard University leading the field. Most of related publications were published in the journals with a focus on sport, medicine, rehabilitation, psychology, and health, as represented by the dual-map overlay. A series of authors and co-cited authors were identified as main contributors in the exercise-depression-teenager domain. Three major clusters were explored based on the reference co-citation analysis: “exercise”, “suicide” and “concussion”. Conclusions: Nowadays’ concerns and hotspots of exercise intervention in depression treatments were summarized by “Individual level”, “Social level”, “Role of exercise”, “Research quality”. We considered that the following four directions were frontiers and future perspectives: “Research on the effect of specific exercise intervention”, “Research on the essence of exercise and sports”, “Research on the combination mode of ‘Exercise + X’ ”, and “Research on the micro and molecular level”, which should receive more attention.